2003
DOI: 10.1046/j.1439-0531.2003.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Measurements and Daily Sperm Output of Tori and Estonian Breed Stallions

Abstract: Kavak A, Lundeheim N, Aidnik M, Einarsson S: Sperm morphology in Estonian and Tori Breed stallions. Acta vet. scand. 2004, 45, 11-18.-The standard procedure for assessing the breeding potential of a stallion includes the parameter total number of spermatozoa classified as morphologically normal. This study investigated sperm morphology of fresh semen in randomly chosen Estonian (E, n=8) and Tori (T, n=7) breed stallions with proven fertility. Two ejaculates were examined from each stallion. An aliquot from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
(10 reference statements)
5
14
3
Order By: Relevance
“…The DSO, calculated as the mean of TSN of days 8–10 was 6.4 × 10 9 . These findings are similar to earlier studies on full‐size horses like Thoroughbred stallions (Sullivan and Pickett 1975) and Tori breed stallions (Kavak et al. 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The DSO, calculated as the mean of TSN of days 8–10 was 6.4 × 10 9 . These findings are similar to earlier studies on full‐size horses like Thoroughbred stallions (Sullivan and Pickett 1975) and Tori breed stallions (Kavak et al. 2003).…”
Section: Discussionsupporting
confidence: 92%
“…(2002), collecting and evaluating total spermatozoa number (TSN) per ejaculate found that DSO determinations can begin as early as day 5 for stallions with smaller testes, and day 6–7 for stallions with larger testes. Kavak et al. (2003), collecting one ejaculate per day for 10 consecutive days found that TSN decreased successively from day 1 to 8 in full‐size horses, and from day 1 to 4 in small‐size horses, thereafter remaining approximately at the same number.…”
Section: Introductionmentioning
confidence: 94%
“…The measurement of testicular volume showed that the left testis is significantly larger than the right one, which was also observed in bulls (Kavac et al 2003) and dogs (Souza et al 2012), demonstrating in that specie an assymetry between right and left sides.…”
Section: Discussionmentioning
confidence: 62%
“…Testis volume has been correlated to total sperm output in the domestic horse [37]. Average volume in the Persian onager (300 cm 3 ) was comparable to those of the domestic horse [69] and donkey [70] and more than twofold greater than that reported for the Cape Mountain zebra (135 cm 3 ) [3] or Przewalski's horse (150 cm 3 ) [7]. These marked species variations in testis size may be related to inherent differences in mating system.…”
Section: Reproduction In the Persian Onagermentioning
confidence: 99%